Kualitas Fisik Biskuit Ela Sagu Fermentasi Mikro Organisme Lokal (MOL) dengan Molases Setelah Penyimpanan - Wewarkey, Emilion; Fredriksz, Shirley; Joseph, Godlief (Jurnal Agrosilvopasture-Tech, 2023)
The purpose of this study was to determine the physical quality of ela sago biscuits fermented by MOL with molasses after being stored. This research was conducted at the Feed Engineering Technology Laboratory, Department of Animal Husbandry Faculty of Agriculture Pattimura University Ambon, which took place from March to May 2023. The material used for this research was fermented MOL sago elas biscuits with molasses which were stored for 2 months. The equipment used is digital scales, mixing bowls, grinders, oven, mixing spoons, biscuit presses, trays, plastic bags, water, aluminum filters, label paper and stationery. The variables observed were the physical quality of the biscuits including color, aroma, texture, weight, and water absorption. Research is an experiment, and the observed data were analyzed descriptively. The results showed that fermented MOL ela sago biscuits with Molasses after 2 months of storage there was a change in physical quality. The physical quality of fermented MOL ela sago biscuits with molasses underwent changes in physical quality in terms of weight, color, aroma, and water absorption.